Single HPV test not useful for predicting CIN2 or worse or for guiding choice of further investigations for women aged 20–59 presenting to NHS Cervical Screening Programme with borderline abnormalities or mild dyskaryosis. Issue 6 (30th July 2010) - Powell, Ned
Abstract : Commentary on: Cotton S Sharp L Little J .; Trial Of Management of Borderline and Other Low-grade Abnormal Smears Group . The role of human papillomavirus testing in the management of women with low-grade abnormalities: multicentre randomised controlled trial . BJOG 2010 ;117 :645 –59 .